Oral contraception and eye disease: findings in two large cohort studies. Issue 5 (1st May 1998) - Vessey, M P; Hannaford, P; Mant, J; Painter, R; Frith, P; Chappel, D
Abstract : AIM: To investigate the relation between oral contraceptive use and certain eye diseases. METHODS: Abstraction of the relevant data from the two large British cohort studies of the effects of oral contraception, the Royal College of General Practitioners' (RCGP) Oral Contraception Study and the Oxford-Family Planning Association (Oxford-FPA) Contraceptive Study. Both cohort studies commenced in 1968 and were organised on a national basis. Between them they have accumulated over 850 000 person years of observation involving 63 000 women. RESULTS: The conditions considered in the analysis were conjunctivitis, keratitis, iritis, lacrimal disease, strabismus, cataract, glaucoma, retinal detachment, and retinal vascular lesions. With the exception of retinal vascular lesions, there was no consistent evidence of important increases in risk of eye diseases in users of oral contraception. There was about a twofold increase in the risk of retinal vascular lesions in recent pill users in both studies (statistically significant only in the RCGP study). The increase was not limited to any specific type of lesion and may well reflect diagnostic bias. CONCLUSION: Oral contraceptive use does not appear to increase the risk of eye disease, with the possible exception of retinal vascular lesions.